Dynamic Kinetic Resolution of Biaryl Atropisomers via Peptide-Catalyzed Asymmetric Bromination - Gustafson, Jeffrey L. (2010)
Despite the widespread use of axially chiral, or atropisomeric, biaryl ligands in modern synthesis, and the occurrence of numerous natural products exhibiting axial chirality, general catalytic methods for the direct asymmetric preparation of this compound class have proven elusive. Here we present a tripeptide-derived small molecule catalyst for the dynamic kinetic resolution of racemic biaryl substrates. The reaction proceeds via an atropisomer-selective electrophilic aromatic substitution reaction employing simple bromination reagents. The result is an enantioselective synthesis that delivers chiral non-racemic biaryl compounds with excellent optical purity and good isolated chemical yields (in most cases >95:5 enantiomer ratio and isolated yields 65 to 87%). A mechanistic model is advanced that explains the basis of selectivity observed.